Migrant Attitudes Towards Democracy in Australia: Excluded or Allegiant Citizens?. (14th October 2021) - Cameron, Sarah; Pietsch, Juliet
Abstract : How do migrants evaluate democracy in Australia? While prior studies have examined migrant support for democracy in Australia, less is known about how migrants evaluate the performance of democracy, as captured by indicators on political trust and satisfaction with democracy. Would migrants have lower levels of political trust and satisfaction with democracy as a result of political exclusion, including under‐representation in parliament? Or would migrants from less democratic countries, socialised in regimes where critical attitudes towards political authorities are discouraged, be more allegiant citizens with relatively positive evaluations of democracy? Using data from the 2010 to 2019 Australian Election Study surveys, combined with Freedom House regime classifications of migrant origin countries, we examine migrant attitudes towards Australian democracy. The results show that while migrants to Australia from other democratic countries have similar attitudes to those born in Australia, those from less democratic countries have higher levels of political trust and satisfaction with democracy. This suggests that despite political exclusion, migrants from less democratic countries are more allegiant citizens than those born in Australia or another democracy.